2001
DOI: 10.1677/joe.0.1700381
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tri-iodothyronine on alternative splicing events in the coding region of cytochrome P450 aromatase in immature rat Sertoli cells

Abstract: Transient postnatal hypothyroidism in male rats induces a prolonged proliferation of immature Sertoli cells. This change in Sertoli cell replication at young ages is coincident with enhanced and prolonged aromatase activity that leads to a marked increase in the conversion of androgens into estrogens. Both events are drastically inhibited by tri-iodothyronine (T 3 ) replacement either in vivo or in vitro. This study, after the immunolocalization of aromatase in cultured rat Sertoli cells, examined the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…In response to T3, testicular expression of Star and Cyp19a1 was up-and down-regulated, respectively in the most of the studied groups (except Star expression in AHA rats). Similar effects of T3 on the testicular Star and Cyp19a1 expression were observed by others (Manna et al 1999, Pezzi et al 2001, Catalano et al 2003. It is also worth to note that inhibition of Cyp19a1 expression by T3 was weaker in NHA compared to that found in the other groups.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In response to T3, testicular expression of Star and Cyp19a1 was up-and down-regulated, respectively in the most of the studied groups (except Star expression in AHA rats). Similar effects of T3 on the testicular Star and Cyp19a1 expression were observed by others (Manna et al 1999, Pezzi et al 2001, Catalano et al 2003. It is also worth to note that inhibition of Cyp19a1 expression by T3 was weaker in NHA compared to that found in the other groups.…”
Section: Discussionsupporting
confidence: 84%
“…However, we were not able to determine any extra nuclear effects of T3 in testes of the studied rats. It cannot be excluded that the effect of T3 on testicular steroidogenesis in heat-acclimated rats would occur using extended tissue incubation with the treatment (Manna et al 1999, Pezzi et al 2001, Catalano et al 2003, Park et al 2014). This notion is supported by observed differences in E2 secretion in response to T3 between the neonatally heat-acclimated (NHA and DA) and the other studied groups (CR and AHA).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, toward the end of the period of Sertoli cell proliferation, FSH-induced aromatase activity begins to decline. Thyroid hormone, which stimulates Sertoli cell differentiation (47), decreases aromatase activity (48,49). We have recently demonstrated that the molecular mechanisms by which this inhibition occurs is through a competition of thyroid receptor ␤ and SF-1 for the same regulatory site NRE (20), demonstrating the crucial role of this site in regulating aromatase expression.…”
Section: Discussionmentioning
confidence: 99%
“…T 3 inhibits CYP19 activity in rat Sertoli cells (28). Pezzi et al (29) suggested that in rat Sertoli cells, T 3 plays a direct role in the regulation of CYP19 promoter activity and induction of altered transcripts coding for truncated and inactive CYP19 protein. It should be interesting to determine whether T 3 influences the promoter activity of CYP19 gene in rat GCs.…”
Section: Discussionmentioning
confidence: 99%